2006
DOI: 10.1111/j.1526-4610.2006.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Zonisamide Prophylaxis in Refractory Pediatric Headache

Abstract: Zonisamide had some efficacy in headache reduction. It was well tolerated with only minor side effects. Further prospective studies with zonisamide are warranted in refractory pediatric headache patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 12 publications
1
22
0
2
Order By: Relevance
“…There is limited information, largely from open label clinical trials, suggesting that zonisamide may be effective in migraine prophylaxis in adults and children (Smith, 2001;Krusz, 2001b;Bigal et al, 2002;Drake et al, 2004;Pakalnis and Kring, 2006;Ashkenazi et al, 2006). Taken together with the available base of information on zonisamide, a case can be made that further study of the drug in controlled trials is warranted.…”
Section: Zonisamidementioning
confidence: 99%
See 1 more Smart Citation
“…There is limited information, largely from open label clinical trials, suggesting that zonisamide may be effective in migraine prophylaxis in adults and children (Smith, 2001;Krusz, 2001b;Bigal et al, 2002;Drake et al, 2004;Pakalnis and Kring, 2006;Ashkenazi et al, 2006). Taken together with the available base of information on zonisamide, a case can be made that further study of the drug in controlled trials is warranted.…”
Section: Zonisamidementioning
confidence: 99%
“…Evidence from double blind randomized placebo-controlled studies also support the effectiveness of gabapentin in migraine prophylaxis (Di Trapani et al, 2000;Mathew et al, 2001) and it is considered a third line agent by BASH. Less robust clinical studies have indicated that carbamazepine (Rompel et al, 1970), lamotrigine (Steiner et al, 1997;D'Andrea et al, 1999;Lampl et al, 2005;Gupta et al, 2007), zonisamide (Drake et al, 2004;Pakalnis and Kring, 2006) and levetiracetam (Brighina et al, 2006) may also be effective in the treatment of migraine. A metaanalysis by the Cochrane Collaboration confirmed that as a class AEDs reduce migraine frequency and are relatively well tolerated (Chronicle and Mulleners, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective chart review (class IV) of refractory headache patients (6 with episodic migraine, 2 with chronic migraine, 4 with chronic tension-type headache) treated with zonisamide (mean dose of 5.7 mg/kg/day), 8 out of 12 patients showed a positive response to zonisamide (450% reduction in headache frequency when compared to baseline) [Pakalnis and Kring, 2006]. Of the 4 non-responder patients, 3 had chronic tension-type headache.…”
Section: Zonisamidementioning
confidence: 99%
“…It was studied retrospectively in 12 pediatric headache patients with mixed headache types (average age 13.5 years) [Pakalnis and Kring, 2006]. Headaches were reduced from baseline and the drug side effects were mild, namely weight loss and behavioral changes.…”
Section: Anti-epileptic Drugsmentioning
confidence: 99%